2014
DOI: 10.3390/s140609369
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Function in Atomic Force Microscopy Applied to a Liquid Environment

Abstract: Scanning specimens in liquids using commercial atomic force microscopy (AFM) is very time-consuming due to the necessary try-and-error iteration for determining appropriate triggering frequencies and probes. In addition, the iteration easily contaminates the AFM tip and damages the samples, which consumes probes. One reason for this could be inaccuracy in the resonant frequency in the feedback system setup. This paper proposes a frequency function which varies with the tip-sample separation, and it helps to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…When the tip shifts to the left ( Figure 4 b–d), the vorticity increases on the right side of the specimen because the geometric gap between the tip and specimen is irregular, which results in complex vorticity. This phenomenon was also found for a planar specimen, as shown in Figure 2b of [ 5 ].…”
Section: Numerical Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…When the tip shifts to the left ( Figure 4 b–d), the vorticity increases on the right side of the specimen because the geometric gap between the tip and specimen is irregular, which results in complex vorticity. This phenomenon was also found for a planar specimen, as shown in Figure 2b of [ 5 ].…”
Section: Numerical Resultssupporting
confidence: 69%
“…Notably, this distortion of surface morphology is different from the geometric effect between tip and specimen in air [ 4 ]. Numerous studies have discussed probe hydrodynamics [ 1 , 5 , 6 ], which are known to affect a probe’s natural frequencies [ 1 , 7 ]; however, few studies have focused on the specimen pressure caused by tips [ 8 ]. The authors of the present study demonstrated that the liquid pressure varies with the tip geometry; furthermore, the maximum hydrodynamic pressure caused by a cone-shaped tip is approximately 0.5 Pa, and this can predeform a membrane by several nanometers before the tip taps its surface [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such studies, researchers have mainly focused on the vibrational properties of the CNTs in order to design different types of sensors [2]. CNT resonators have been used so far in many instruments for sensing very small mass [1], force [3], detection of gas atoms [4], and AFM in fluid environments [5]. CNT resonators have been used so far in many instruments for sensing very small mass [1], force [3], detection of gas atoms [4], and AFM in fluid environments [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the vibrating probe produces pressure and vorticity at the edges between the tip and the beam, and these affect the pressure on the specimen. Many studies have discussed the dynamics of probes in a liquid environment [1,4], but few have focused on pressure caused by these tips. We believe the liquid pressure and vorticity induced by the vibrating tip may deform the geometric surface of the specimen, especially when the tip and specimen are close.…”
Section: Introductionmentioning
confidence: 99%